Solid-State Fermentation of Soybean Meal with Edible Mushroom Mycelium to Improve Its Nutritional, Antioxidant Capacities and Physicochemical Properties - Jian Wang; Quanjin Jiang; Zhenyu Huang; Yan Wang; Hynek Roubik; Kai Yang; Ming Cai; Peilong Sun (Fermentation, 2023)
Soybean meal is a class of by-products obtained from the processing of soybean products. Despite its high nutritional value, the presence of glycoside isoflavones limits human use of soybean meal. This study evaluated the effect of solid-state fermentation (SSF) with different edible mushroom mycelia (Pleurotus ostreatus, Hericium erinaceus, and Flammulina velutipes) on the proximate composition, antioxidant properties, and physicochemical properties of fermented soybean meal powder (SP). The results revealed that fermented SP had a higher nutritional value when compared to SP. P. ostreatus was the most pronounced among the three species. Crude protein content was found to have increased by 9.49%, while the concentration of glutamate and aspartic acid increased by 23.39% and 23.16%, respectively. SSF process significantly increased the total polyphenol content (TPC) and aglycone isoflavone content by 235.9% and 324.12%, respectively, resulting in increased antioxidant activity (evaluated by the DPPH, •OH, ABTS+ assays). Microstructural changes in fermented SP and nutrient degradation and utilization were observed. Thus, fermented SP can be used as a raw material with enhanced nutritional properties to develop new functional foods, such as plant-based foods represented by plant meat. It provides a promising approach for increasing the added value of soybean meal.